Povezanost izbranih motoričnih in morfoloških spremenljivk s tekmovalno uspešnostjo dveh generacij mladih alpskih smučarjev - Lešnik, Blaž (Šport (Ljubljana), 2018)
Based on the present study we observed the dynamics of the variations to motor and morphological status of two generations of young alpine skiers in ten-year period from 2001 to 2010. The subject sample included 58 young alpine skiers who represented two U-14 generations (Gen1 = 2001/02; Gen2 = 2009/10) in category of older boys in official alpine ski competition system of Ski association of Slovenia (SZS). The developed Model of potential success (MPU) comprised 17 motor and 7 morphological variables, on other side the criterion variable is represented by a sum of points on competitions. By using Pearson%s correlation coefficients (r), we attempted to find the correlation between individual variables (1st Level of MPU) and success in competitions by Gen1 and Gen2. We determined that in ten year period the number of statistically significant correlations between individual motor variables and the success criterion increased from 5 to 12 (Gen1 = 5; Gen2 = 12). The results were also confirmed by calculating the multiple correlation coefficients (R), which are statistically significant in both generations (MOT 2001/02: R2 adj. = 0,82, R = 0,98, p = 0,04 in MOT 2009/10: R2 adj. = 0,64, R = 0,90, p = 0,00). It was also proved that the number of statistically significant connecitons between various morphological variables and criterion decreased from 4 to 3 (Gen1 = 4; Gen2 = 3). In this case the calculation of coefficient of multiple correlation nevertheless shows a high and statistically significant correlation with the criterion variable only in younger generation Gen2 (MORF 2001/02: R2 adj. = 0,19, R = 0,68, p = 0,18 in MORF 2009/10: R2 adj. = 0,36, R = 0,70, p = 0,00). The results of the study represent a useful contribution to the development of the theory and methodology of preparing the young competitors and to the future upgrading of the MPU in competitive alpine skiing.
Keywords: alpsko smučanje; mlajše kategorije; morfološke značilnosti; motorične sposobnosti; tekmovalna uspešnost; trening; zimski športi